2018
DOI: 10.1002/jmrs.269
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of non‐accidental injury; what is clinical best practice?

Abstract: Non‐accidental injury (NAI) remains the leading cause of morbidity and mortality in children. Fractures are the second most common findings of NAI, after cutaneous lesions such as bruises and contusions. Imaging in NAI remains a controversial issue with little agreement concerning how, when and what imaging modalities should be used in the investigation of suspected cases. This review addresses the radiological investigations and findings of NAI, and the differential diagnoses of these findings. Adherence to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…The radiation exposure associated with bone scans, when considered against the limited additional information they provide, tips the balance away from their routine use 1. However, when a child presents with suspected abuse and meets criteria for CT scan and skeletal survey, the potential benefits to that child of those two investigations will always outweigh the potential long-term risk from the radiation doses described in this paper 22 36…”
Section: Discussionmentioning
confidence: 98%
“…The radiation exposure associated with bone scans, when considered against the limited additional information they provide, tips the balance away from their routine use 1. However, when a child presents with suspected abuse and meets criteria for CT scan and skeletal survey, the potential benefits to that child of those two investigations will always outweigh the potential long-term risk from the radiation doses described in this paper 22 36…”
Section: Discussionmentioning
confidence: 98%
“…Radiology provides essential medical imaging procedures that aid in uncovering various concealed non-cutaneous lesions in a patient of suspected abuse, and these radiological findings should be explained in view of psychosocial history and reporting should focus on addressing anomalies, differential diagnoses, adequacy of imaging, and appropriate communication of NAT suspicion. Radiologists can additionally provide opinions on the credibility of the radiographs by identifying important landmarks and make comments on the suggestive mechanism of injury [ 75 ]. Radiological lesions of abuse can be broadly classified into three categories: osseous, visceral, and traumatic head injury due to child maltreatment (THI-CM), also known as abusive head trauma (AHT).…”
Section: Reviewmentioning
confidence: 99%
“…In 2008, the RCR and Royal College of Paediatrics and Child Health suggested that this radiographic series would typically have an effective radiation dose of 0.9-1.8 mSv [2]. The RCR also advocates follow-up imaging to better demonstrate healing fractures and some departments continue to perform scintigraphy, therefore the effective dose can be as high as 3 mSv [3]. Due to the frequency of uncooperative younger patients, the skill level of the radiographer in achieving diagnostic images at the lowest patient radiation dose is of particular importance [4].…”
Section: Introductionmentioning
confidence: 99%